Historical Sociology of State Formation in the Horn of Africa - Bereketeab, Redie. author. (orcid)0000-0002-4378-1893 Link aut Link
XIII, 247 p. 4 illus., 3 illus. in color.
Keywords: This book analyses the historical sociology of state formation in the Horn of Africa. It examines the genesis, trajectories, processes, routes and consequences of the evolution of state formation. Three analytical and explanatory models explain the process of state formation in the HOA: proto-state, colonial and national liberation. The models, heuristically and innovatively, provide understanding, interpretation and analysis of state formation. While the proto-state model explicates an indigenous historical process of state formation, the colonial model refers to an externally designed and imposed process of state formation. The national liberation model concern state formation conducted under liberation movement and ideology. The distinct significance of these models is that collectively they generate sufficient analysis of state formation. They are also unique in that they have never been employed as aggregate analytical and explicative instruments to address the predicament of state formation in the Horn of Africa. Redie Bereketeab is Associate Professor of Sociology and Senior Researcher at the Nordic Africa Institute at Uppsala University, Sweden. His latest publications include: National Liberation Movements as Government in Africa (2019), and Alternatives to Neoliberal Peacebuilding and Statebuilding in Africa (2021). His research interest include political sociology, development sociology, African studies, conflict, peacebuilding, regional integration.